Comparative Study of Magnetic Pc1 Pulsations between Low Latitudes and High Latitudes: Source Region and Propagation Mechanism of the Waves Deduced from the Characteristics of the Pulsations at Middle and Low Latitudes - Kawamura, Makoto; Kuwashima, Masayuki; Toya, Takeshi (1981)
P(論文) The purposes of the present paper are to present some interesting morphological features of pc1 pulsations observed at low latitudes and to propose the most plausible model of generation and propagation of the pulsations. Comparison between the low-latitude pc1 and the high-latitude one will be done in our joint paper (KUWASHIMA et al., 1981). In this paper, occurrence characteristics, the most important factors, of the pulsations are mainly investigated. In the first place, some statistical features of the pulsations are shown on the basis of data obtained at Memambetsu, the northernmost one of the Japanese chain stations, during two-years period from June 1967 to May 1969. And the features of the diurnal and seasonal variations are compared with those of the electron density of the ionospheric F2 layer at Wakkanai which is located at a distance of about 200km from Memambetsu. Next, conjugate relationships of the pulsations at middle and low latitudes are analyzed statistically on the basis of data obtained at Memambetsu, Japan and Newcastle and Hobart, Australia for the same two-years period. Relations between the occurrence and the development of the ring current (Dst) are also discussed. Moreover, the above conjugate relationships of the pc1 occurrence at middle and low latitudes are investigated in more detail in comparison of dynamic spectra obtained at Memambetsu and the Australian longitudinal chain stations, Mundaring, Woomera, Newcastle and Auckland, for the period of April 1-30,1977. These results suggest that the low-latitude pc1 has its source regien at the plasmapause latitudes and propagates to lower latitudes approximately along the connected geomagnetic meridians through the ionospheric wave duct. Finally, a plausible model of the generation and propagation is proposed. departmental bulletin paper